1985
DOI: 10.1017/s0266466600011117
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Theory of Consistent Estimation for Parametric Models

Abstract: Ve present a general theory of consistent estimation for possibly misspecified parametric models based on recent results of Domowitz and White [17].This theory extends the iinification of Burguete, Gallant and Souza [12] by allowing for heterogeneous, time dependent data and d3mamic models. The theory is applied to yield consistency results for quasi-maximum likelihood and method of moments estimators. Of particular interest is a new generalized rank condition for identifiability. SEP 3 19851 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…In addition, Bates and White (1985) extend the theory to general quasi-M-estimators, by introducing discrepancy functions. Now, we add more randomness to the misspecification theory, which enables our applications to stochastic volatility models, where the parameter of interest itself is random.…”
Section: Asymptotic Theory Of Quasi-m-estimatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Bates and White (1985) extend the theory to general quasi-M-estimators, by introducing discrepancy functions. Now, we add more randomness to the misspecification theory, which enables our applications to stochastic volatility models, where the parameter of interest itself is random.…”
Section: Asymptotic Theory Of Quasi-m-estimatorsmentioning
confidence: 99%
“…In these articles, the framework of misspecified estimation has been built and its close connection with Kullback-Leibler Information Criterion (KLIC) (see Kullbacks and Leibler (1951)) has been illustrated. Since these seminal works, Domowitz and White (1982) and Bates and White (1985) have extended the consistency results of the QMLE with i.i.d. models to various cases including dependent observations, Quasi-GMM-estimators, and Quasi-M-estimators.…”
Section: Introductionmentioning
confidence: 99%
“…Under very general conditions, it can be shown that σ -2 jT -1/T ΣS j t r 0 with probability one. A similar formulation of asymptotically valid moment conditions appears in the theoretical treatment of Bates and White (1985), for example. Equations (A7) are consistent with the theoretical model structure, as long as almost surely, for example, which holds as long as 1/T Σω t z t -1/T Σω -T z t r 0 base-level variances (and their averages) are …”
Section: Appendix: the Model And Variance Decompositionmentioning
confidence: 94%
“…Although it is beyond the scope of this paper, we suggest two directions to relax this assumption. First, Assumption 1(b) may be generalized by using the notion of ''identifiably unique parameters'' in Domowitz and White (1982, Definition 2.1), which are not required to converge to a limit (see also Bates and White (1985) for a detailed discussion on consistency). Second, a recent paper by Shi (2009) proposed the notion of ''pseudo-true sets'' 10 In MATLAB, fmincon allows nonlinear constraints.…”
Section: Asymptotic Propertiesmentioning
confidence: 99%